Pengaruh Lokasi dan Kualitas Produk terhadap Keputusan Pembelian Pelanggan pada Toko Exsha Frozen Food Cinere - Pepi Lestari Zalukhu; Nani Sriyani (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This study aims to determine the influence of location and product quality on consumer purchase decisions at the Exsha Frozen Food Cinere Store. This study used a quantitative method by distributing questionnaires to 100 respondents. Data analysis techniques include validity, reliability, classical assumption test, multiple linear regression, as well as t-test and f-test. The results of the t-test showed that the location variable (X1) had a t-calculated value of 11.415 > t-table 1.984 and a significance of 0.000 < 0.05 which means that location has a significant effect on the purchase decision. The product quality variable (X2) also showed a tally of 17.889 > t-table of 1.984 and a significance of 0.000 < 0.05, which means that product quality has a significant effect on purchasing decisions. The results of the f-test showed that the location and quality of the product simultaneously had a significant effect on the purchase decision, with an f-count of 160.790 > f-table of 3.09 and a significance of 0.000 < 0.05. The value of the determination coefficient (R square) of 0.555 indicates that 55.5% of purchase decisions are influenced by the location and quality of the product, while the remaining 44.5% are influenced by other variables that were not studied.